Cutaneous metastasis of inflammatory breast carcinoma mimicking an erythema annulare centrifugum: a sign of locally recurrent cancer. (20th October 2016) - Sabater, V.; Ferrando, F.; Morera, A.; Palomar, L.
Summary: Erythema annulare centrifugum (EAC) is a clinical reaction pattern that includes lupus erythematosus, spongiotic dermatitis (particularly pityriasis rosea), pseudolymphoma and cutaneous B‐cell lymphoma. However, it can be the result of cutaneous metastasis by an internal carcinoma. We present the case of a 38‐year‐old woman with bilateral inflammatory breast cancer following multimodal therapy. After chemotherapy, the patient developed EAC on her back, clinically suspect of subacute cutaneous lupus erythematosus. A skin biopsy of annular lesion revealed dermal lymphatic infiltration by inflammatory breast carcinoma. Immunohistochemically, HER2 overexpression and negativity for hormone receptor are the hallmarks of this disease. Cutaneous metastasis by inflammatory breast carcinoma mimicking EAC is rare, and it has not been described in extramammary locations. Its recognition by the dermatologist is important because it can be a clinical manifestation of locally recurrent cancer. Abstract : Clickhere for the corresponding questions to this CME article.